The collective vibration modes of hydrogen bonds as a gauge of water states in fruits and leaves - Kornienko, M.E.; Kutovyi, S.Y.; Piddubetska, O.V.; Smoljar, N.P. (Біополімери і клітина, 2006)
The new conception of the collective vibration modes (CVM) of the water medium is used to study water states in tissues (leaves and fruit). The CVM of the hydrogen bond (HB) nets were studied by the methods of the Raman and infrared (IR) spectroscopy in the region of the low-frequency LO and TO modes and high-frequency summary tones of these modes with fundamental vibrations. The frequency and intensity changes in the collective modes in comparison with distilled water are indicative of the HB nets ordered or disordered. It was found that in plant tissue the water can be both in disordered state as compared to distilled water and in more collectivized state. The existence of four different water states in leaves has been established. Концепцію колективних коливальних мод (ККМ) водних середовищ застосовано для вивчення станів води у тканинах рослин (листки і плоди). Методами раманівської спектроскопії та інфрачервоного (14) поглинання досліджено ККМ сітки водневих зв'язків в області низькочастотних ТО і LO мод, високочастотних сумарних тонів цих мод з фундаментальними коливаннями. Знайдено, що в листках і соках рослин вода може існувати у менш зв'язаному стані порівняно з дистильованою і в колективізованіиіому стані. В листках рослин нами виявлено існування чотирьох різних структурних станів води, які можна ідентифікувати за параметрами смуг (інтенсивність і частотний зсув) обертонів та складних тонів у спектрах 14-поглинання Концепция коллективных колебательных мод (ККМ) водных сред использована для изучения состояний воды в тканях растений (листья и плоды). Методами романовской спектроскопии и инфракрасного (ИК) поглощения исследованы ККМ сетки водородных связей в области низкочастотных ТО и LO мод, высокочастотных суммарных тонов этих мод с фундаментальными колебаниями. Обнаружено, что в листьях и соках растений вода может находиться в менее связанном состоянии сравнительно с дистиллированной и в более коллективизированном состоянии. В листьях растений выявлено существование четырех различных структурных состояний воды, которые можна идентифицировать по параметрам полос (интенсивность и частотный сдвиг) обертонов и составных тонов в спектрах ИК-поглощения.